EVALUASI PENERAPAN PILOT PROJECT GLOBAL BUDGET SEBAGAI SISTEM PEMBAYARAN KLAIM PADA RSUD WATES - Handayani, Mega; Ilmi, Laili Rahmatul; Mubarrok, Zennul Mubarrok1 (Jurnal Ekonomi Kesehatan Indonesia, 2023)
Claims payment for health services is one of the factors that affect the financial health of a hospital. Indonesia itself has experienced several changes to the existing payment system. BPJS-K started an operational study on the implementation of the INA-CBGs and the Global Budget mixed-method payment system since 2018 with three stages in five districts/city in Indonesia. This study aims to evaluate the implementation of the Global Budget system at RSUD Wates in Kulon Progo Regency that appointed as a BPJS-K pilot project. This research is qualitative research and data collection was carried out by studying documents and interviews. As a result, it is known that in 2021 RSUD Wates experienced a budget surplus and on the contrary, in 2022 the hospital experienced a significant deficit. However, the efficiency of health service financing at RSUD Wates cannot be evaluated as a whole in the implementation of the global budget trial. The implementation of the global budget at RSUD Wates was carried out under uncommon conditions where the COVID-19 pandemic occurred in 2020-2022 so that the data on the number of patients became less relevant as a reference for budget calculations. In addition, all stages in the trial have not been fully implemented. Coordination and the role of policy makers are expected to be improved so that the competence and efficiency of hospital health services can be optimized.